(untitled) (Reflection and Critique Law Magazine, 2020)
This article proposes to study the difficulties to the occurrence of access to justice and popular action as a tool to ensure this right. The purpose of the research is to identify how free access to justice is a guaranteed right of the Federal Constitution of 1988 to all those who were victims of violation of some right. In addition, the present article aims to analyze the norms and the way in which those who have active legitimacy to propose action with the objective of guaranteeing the protection of public patrimony, administrative morality and the environment. The methodology used in the research was the methodology of the bibliographic review, through the analysis of books and articles published physically or through the internet.